Homeschooling or education besieged in the intèrieur: notes from Walter Benjamin (Práxis Educativa, 2020)
This paper studies the homeschooling movement from the perspective of Walter Benjamin’s fragmentary hermeneutics. The objective is to define this movement as an epiphenomenon linked to the loss of communicability and poor experience that configures modernity, especially in the current period characterized by the control of education policies by financial hegemony’s neoliberalism. This text is underpinned by a Benjaminian methodology in order to construct monadological structures that characterize domestic education as a phenomenon derived from the increasingly accentuated process of interiorization of the bourgeois society, which assigns the private sphere to an important achievement of the liberal revolution itself: the modern universal school. As a provisional result, it appears that the homeschooling movement is another expression of the reactionary and solipsistic physiognomy of the bourgeois intèrieur.Keywords: Homeschooling. Benjaminian Hermeneutics. Neoliberalism.